2021
DOI: 10.1093/pasj/psab116
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of infrared spectra of interstellar PAH molecules with N, NH, and NH2 incorporation

Abstract: This work presents theoretical calculations of infrared spectra of nitrogen (N)-containing polycyclic aromatic hydrocarbon (PAH) molecules with the incorporation of N, NH, and NH2 using density functional theory (DFT). The properties of their vibrational modes in 2–15 μm are investigated in relation to the Unidentified Infrared (UIR) bands. It is found that neutral PAHs, when incorporated with NH2 and N (at inner positions), produce intense infrared bands at 6.2, 7.7, and 8.6 μm that have been normally attribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
0
17
0
2
Order By: Relevance
“…There are two most appropriate forms of PANHs-(i) PAHs having N within the PAH skeleton or N-substituted PAHs (N-PAHs, Fig. 1) (Hudgins et al 2005;Ricca et al 2021;Vats et al 2022) and, (ii) PAH nitriles or CN-attached PAHs (CN-PAHs, Fig. 1).…”
Section: Sample and Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two most appropriate forms of PANHs-(i) PAHs having N within the PAH skeleton or N-substituted PAHs (N-PAHs, Fig. 1) (Hudgins et al 2005;Ricca et al 2021;Vats et al 2022) and, (ii) PAH nitriles or CN-attached PAHs (CN-PAHs, Fig. 1).…”
Section: Sample and Theoretical Methodsmentioning
confidence: 99%
“…The GAUSSIAN 09 (Frisch et al 2009) suite of programs was used to compute each molecule's geometry, rotational constants, quadrupole coupling constants, quartic centrifugal distortion constants and dipole moments using Density Functional Theory (DFT) with anharmonic vibrational frequency calculations. DFT has been widely utilized in rotational spectroscopy of interstellar Ncontaining PAHs to determine the molecular or spectroscopic constants (Kisiel et al 2003;McNaughton et al 2008;Pirali et al 2015;McNaughton et al 2018), as well as to compute their vibrational modes (Hudgins et al 2005;Vats et al 2022;Ricca et al 2021). The use of B3LYP functional with the 6-311+G(d,p) basis set or the correlation-consistent polarized triple valence basis set (cc-pVTZ) are found effective for studying the molecular or spectroscopic constants of CN-PAHs (McNaughton et al 2018), whereas the MP2/6-31G(d,p) combination is found better for quinoline (Kisiel et al 2003).…”
Section: Sample and Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, N−H stretching features fall near 2.9 μm (2900 nm) 47,58 and the nondetection of N−H vibrational modes in observations restricts the contribution of N−H-containing PAHs. 47 Ricca et al 58 derived the upper limit for their possible contribution to the interstellar, 3.3 (3300 nm) and 6.2 μm bands (6200 nm) as 0.36 and 2.5%, respectively. The PANH species selected for our computational analysis are Nsubstituted coronene (C 24 H 12 ) and N-substituted circumcoronene (C 54 H 18 ).…”
Section: ■ Structure Of Panh Moleculesmentioning
confidence: 99%
“…Several investigations have found that a N atom can be included in the PAH structure. ,, The effect of nitrogen on the vibrational and electronic spectra of PAHs has also been investigated in various theoretical and experimental studies. , While for PANHs, the time-dependent density functional theory (TD-DFT) calculation technique is useful in interstellar cloud modeling, as the knowledge of oscillator strength enhances the understanding of cosmic abundances.…”
Section: Introductionmentioning
confidence: 99%